ANALISIS TATA RUANG KANTOR BAGIAN PERDATA DI PENGADILAN NEGERI KARANGANYAR KELAS II - Try Agustina; Hery Sawiji; Anton Subarno (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
This study aims to find out 1) how to anticipate the incorrect office layout at civil department of Karanganyar state court class II, 2) how to arrange the office equipment which does not place at ergonomically to the officers at Karanganyar state court class II. The research is a qualitative method using a case study approach. Data sources were informants, places, events, and documents. The research sampling was the snowball sampling. Data were collected using observation, interviews and analysis documents. The data were validated using technical triangulation and source triangulation. Data analysis techniques were interactive analysis models. The results of this study show that 1) to anticipate the incorrect office layout at civil department of Karanganyar state court class II is as follows, maximizing the use of existing space at the civil department as needed, designing a good office spatial planning, rearranging the office layout at the civil department by paying attention the workflow principle and the flexible arrangement of office layout. 2) to arrange the office equipment which does not place at ergonomically to the officers is the equipment placement next by the officer in order to minimize the waste of time and energy. The equipment is placed in accordance with the workflow which makes the officers easy to work, announcing and training for officers who cannot operate new machinery or equipment.